Ageism in COVID-Related Newspaper Coverage: The First Month of a Pandemic. (7th June 2021) - Jen, Sarah; Jeong, Mijin; Kang, Hyun; Riquino, Michael
Abstract: Objectives: Media sources have consistently described older adults as a medically vulnerable population during the coronavirus disease 2019 (COVID-19) pandemic, yet a lack of concern over their health and safety has resulted in dismissal and devaluation. This unprecedented situation highlights ongoing societal ageism and its manifestations in public discourse. This analysis asks how national news sources performed explicit and implicit ageism during the first month of the pandemic. Method: Using content and critical discourse analysis methods, we analyzed 287 articles concerning older adults and COVID-19 published between March 11 and April 10, 2020, in 4 major U.S.-based newspapers. Results: Findings indicate that while ageism was rarely discussed explicitly, ageist bias was evident in implicit reporting patterns (e.g., frequent use of the term "elderly, " portrayals of older adults as "vulnerable"). Infection and death rates and institutionalized care were among the most commonly reported topics, providing a limited portrait of aging during the pandemic. The older "survivor" narrative offers a positive alternative by suggesting exceptional examples of resilience and grit. However, the survivor narrative may also implicitly place blame on those unable to survive or thrive in later life. Discussion: This study provides insight for policy makers, researchers, and practitioners exploring societal perceptions of older adults and how these perceptions are disseminated and maintained by the media.